Anti-centromere antibodies target centromere–kinetochore macrocomplex: a comprehensive autoantigen profiling. Issue 5 (18th November 2020) - Kajio, Nobuhiko; Takeshita, Masaru; Suzuki, Katsuya; Kaneda, Yukari; Yamane, Humitsugu; Ikeura, Kazuhiro; Sato, Hidekazu; Kato, Shin; Shimizu, Hiroyuki; Tsunoda, Kazuyuki; Takeuchi, Tsutomu
Abstract : Objectives: Anti-centromere antibodies (ACAs) are detected in patients with various autoimmune diseases such as Sjögren's syndrome (SS), systemic sclerosis (SSc) and primary biliary cholangitis (PBC). However, the targeted antigens of ACAs are not fully elucidated despite the accumulating understanding of the molecular structure of the centromere. The aim of this study was to comprehensively reveal the autoantigenicity of centromere proteins. Methods: A centromere antigen library including 16 principal subcomplexes composed of 41 centromere proteins was constructed. Centromere protein/complex binding beads were used to detect serum ACAs in patients with SS, SSc and PBC. ACA-secreting cells in salivary glands obtained from patients with SS were detected with green fluorescent protein-fusion centromere antigens and semiquantified with confocal microscopy. Results: A total of 241 individuals with SS, SSc or PBC and healthy controls were recruited for serum ACA profiling. A broad spectrum of serum autoantibodies was observed, and some of them had comparative frequency as anti-CENP-B antibody, which is the known major ACA. The prevalence of each antibody was shared across the three diseases. Immunostaining of SS salivary glands showed the accumulation of antibody-secreting cells (ASCs) specific for kinetochore, which is a part of the centromere, whereas little reactivity against CENP-B was seen. Conclusions: We demonstrated that serum autoantibodies target the centromere–kinetochore macrocomplex in patients with SS, SSc and PBC. The specificity of ASCs in SS salivary glands suggests kinetochore complex-driven autoantibody selection, providing insight into the underlying mechanism of ACA acquisition.